INSIDE VIEW ON POLITICAL HISTORY OF RUSSIA IN THE 1990s AS A TOOL OF DEMYTHOLOGIZATION - I. O. Viatkin; A. V. Maksimov (Сравнительная политика)
The purpose of the present research is to explore nature and degree of the subjectivity of the constellation of stereotypes, myths united by the “dashing nineties” cliché that surround the period of 1990s of the Russian history.The ﬁrst part of the article is devoted to the literature review on the ontology of social “mythologization” of historical events. It reveals that subjective interpretation of the past (“construction of history”) is signiﬁ cant as a tool for legitimizing the present, primarily the political. In addition, review reveals a number of persistent historical narratives, associated with the 1990s , that have been circulating in Russian political discourse.The methodological basis of the work are in-depth interviews with people who held positions in Russian ofﬁ cial bodies throughout the 1990s . Informants disclosed that life difﬁ culties that the majority of citizens had faced during the 1990s , coupled with the usage of the negative ideological stamp of “dashing 90s” by the contemporary Russian political regime are the main causes of mythologization. In turn, respondents pointed out that each particular mythology mentioned are the simpliﬁ ed derivatives of the reception of events by ordinary people suffering from a ﬂ awed and incomplete understanding of what was happening.In conclusion, it is inferred that the presence of a quasi-ofﬁ cial state position that reinforce the philistine view of the 1990s imposes certain restrictions on the scope and intensity of public discussion about the role of the 1990s in the history of the Russian state, which deﬁ nitely hinders the demythologization of this period in the mass consciousness.